New pecularities of generation of frictiou-induced leyers on the wear surface of Cо-TіC cemented carbides - Tisov, O.V. (Problems of Tribology, 2016)
The work focuses the new pecularities of tribological processes running on the friction surface of Со-ТіС cemented carbides. It was found thet the formed friction-induced oxide layer corresponds tu the rule of positive gradient of mechanical properties; the stages of it formation were established. The reason of wear increment at temperature above 950 оС was pointed